Phytoplankton counts and nutrient concentration in shrimp Litopenaeus vannamei culture with Gracilaria birdiae in integrated multi-trophic biofloc system - Clarissa Vilela Figueiredo da Silva Campos; Alfredo Olivera Gálvez; Luís Otávio Brito; Renata da Silva Farias (PANGAEA, 2018)
Data regarding to phytoplankton, until genus level, found in L. vannamei culture with red seaweed G. birdiae in integrated multi-trophic biofloc system (IMBS) during 42 days. There was tested three algae densities: 2.5; 5.0 and 7.5 kg.m-3, that are respectively LG2.5; LG5.0 and LG7.5 treatments adding a control in biofloc system (LB).
Supplement to: Campos, Clarissa Vilela Figueiredo da Silva; Moraes, Laenne Barbara Silva de; Farias, Renata da Silva; Severi, William; Brito, Luís Otávio; Gálvez, Alfredo Olivera (2019): Phytoplankton communities in aquaculture system (integration of shrimp and seaweed). Chemistry and Ecology, 35(10), 903-921, https://doi.org/10.1080/02757540.2019.1668378